Geochemical bioenergetics during low‐temperature serpentinization: An example from the Samail ophiolite, Sultanate of Oman. Issue 7 (26th July 2017) - Canovas, Peter A.; Hoehler, Tori; Shock, Everett L.
Abstract: Various classes of microbial and biomolecular evidence from global studies in marine and continental settings are used to identify a set of reactions that appear to support microbial metabolism during serpentinization of ultramafic rocks. Geochemical data from serpentinizing ecosystems in the Samail ophiolite of Oman are used to evaluate the extent of disequilibria that can support this set of microbial metabolisms and to provide a ranking of potential metabolic energy sources in hyperalkaline fluids that are direct products of serpentinization. Results are used to construct hypotheses for how microbial metabolism may be supported in the subsurface for two cases: ecosystems hosted in rocks that have already undergone significant serpentinization and those hosted by deeper, active serpentinization processes. Key Points: Thermodynamic modeling allows ranking of chemical energy supplies that support life generated through serpentinization Autotrophic methanogenesis may occur very close to the surface where H2 (aq) from depth encounters CO2 from the atmosphere Likelihood that nitrogen‐cycle reactions are capable of supporting microbial metabolism during serpentinization in the subsurface Plain Language Summary: Chemical energy that supports communities of microbes becomes available when water reacts with rock. A striking example occurs when water reacts with the type of rock normally found in the Earth's mantle. The resulting process called "serpentinization" releases energy that microbes can harvest to grow and reproduce. A classic example of serpentinization occurs in mantle rocks exposed in Oman. This work involved sampling of water from springs in Oman, geochemical analyses in the lab, and computer models to determine the energy supplies. Comparisons allow ranking among energy sources and predictions of how the reactions of water with rocks support different microbial communities both at the surface and deep below the surface. This work will help guide microbiological studies of serpentinization, which are ongoing in numerous locations around the world. In addition, serpentinization may supply energy to microbial communities on other planets, especially the icy worlds of the outer solar system, so the results form this study may also guide space exploration.